Import substitution of geoinformation technologies in the educational process of state-owned Russian universities - Andryushchenko, Vladimir Y. (Известия Саратовского университета. Новая серия: Серия Науки о Земле, 2025)
Introduction. The article presents the current socio-political situation and its impact on the market of geoinformation technologies. The requirements of the legislation of the Russian Federation for software purchased for government needs are given. The problem of transition to domestic geoinformation technologies is formulated. Conditions that determine the possibility of solving the problem. The main conditions that need to be created to resolve the problem as soon as possible and their interrelationship have been identified. Comparative analysis of modern GIS capabilities.The possibilities of the most common domestic and foreign GIS systems, their main advantages and disadvantages over each other are considered. Based on the analysis of their capabilities, two options for import substitution of geoinformation technologies in universities are proposed. The problem of financing. A general comparison of the functionality of the paid and free versions of the software is carried out. The cost of some GIS components of domestic and foreign development is given. Creating a system of incentives in universities.The influence of software import substitution on the change in the volume of methodological activities of the teaching staff is considered. Measures are proposed to increase the interest of the teaching staff in solving this problem as soon as possible. Conclusion.The conclusion is made about the relevance of the task and the reality of its implementation. Measures to solve it are proposed.